Risk and outcome of COVID-19 infection in sarcoidosis patients: results of a self-reporting questionnaire - Baughman, Robert P.; Lower, Elyse; Buchanon, Mindy; Rottoli, Paola; Drent, Marjolein; Sellares, Jacobo; Terwiel, Michelle; Elfferich, Marjon; Francesqui, Joel; Barriuso Cabrerizo, Maria Rita; Sweiss, Nadera; Martone, Filippo; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: It has been suggested that sarcoidosis patients, especially those on immunosuppressive medications, are at increased risk for COVID-19 infection and more severe disease. Methods: A questionnaire was developed in four languages (English, Dutch, Italian, and Spanish). The questionnaire queried whether patients had been infected with COVID-19 and outcome of the infection. Risk factors for COVID-19 infection were collected. Results: A total of 5200 sarcoidosis patients completed the questionnaire with 116 (2.23%) reporting infection and 18 (15.8%) required hospitalization. Increased hazard ratio (HR) for COVID-19 infection were seen for those with a COVID-19 infected roommate (HR=27.44, p<0.0001), health care provider (HR=2.4, p=0.0001), pulmonary sarcoidosis (HR=2.48, p=0.001), neurosarcoidosis (HR=2.02, p<0.01), or rituximab treatment (HR=5.40, p<0.0001). A higher rate of hospitalization was found for those with underlying heart disease (HR=3.19 (1.297-7.855), p<0.02). No other feature including race, other immunosuppressive agent, age, or underlying condition was associated with a significant increased risk for infection or more severe disease. Conclusion: The overall rate of COVID-19 was 2.23%, suggesting an increased rate of COVID-19 infection. However, when an analysis of the questionnaires of sarcoidosis and non-sarcoidosis patients was performed in one localized area over this time period, the rate of COVID-19 infection was similar in both groups. Sarcoidosis patients who cohabitated with COVID-19 infected individuals, worked in health care, had pulmonary or neurologic sarcoidosis, or were treated with rituximab had an increased risk for COVID-19 infection. No significant increased risk for hospitalization could be identified based on age, race, gender or any specific immunosuppressive treatment.